Assessing User Experience of ChatGPT Website Employing the User Experience Questionnaire (UEQ) - Dila Okta Dwi Putri; Dinda Lestarini (Sistemasi: Jurnal Sistem Informasi)
One form of information technology advancement is the use of AI in website development, one of which is ChatGPT website. ChatGPT has a poor user experience in various aspects, so it is necessary to evaluate the user experience on the ChatGPT website using User Experience Questionnaire (UEQ). The attractiveness variable obtained a positive evaluation value of 1.503. The perspicuity variable obtained a positive evaluation value of 1.661. The efficiency variable obtained a positive evaluation value of 1.615. The dependability variable obtained a positive evaluation value with an overall average value of 1.286. The stimulation variable obtained a positive evaluation value of 1.182. The novelty variable obtained a positive evaluation value of 0.942. The ChatGPT website has shown good quality because it has a positive evaluation value from user assessments. However, in the attractiveness, dependability, and novelty variables, there are still several items that get neutral ratings. So product improvements are still needed to increase user satisfaction.